FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN EFEK PAPARAN MEDIA PORNOGRAFI PADA REMAJA DI SMK SWASTA SE-KABUPATEN BEKASI - Dewa Ayu Sri Saraswati (STIKes IMC Bintaro, 2018)
The purpose of this research is to find and look for the related factors of pornography media explanation effect to the teenager students at private vocational school in the bekasi area in 2010. The writer applied the cross sectional analytic design method to this research with the stratified multiple stages random sampling technique. This research was done at SMK AL–AMIN and SMK TEKNOLOGI AS–SALAM while the collecting data process was done on December of 2010. The research population was 120 respondents. The applying analysis used the univariate analysis, bivariate analysis with the chi square examination and for the multivariate analysis used logictic analysis in order to connect the independent variable with dependent variable and to get the dominant variable which is related to the factors of pornography media explanation effect. The analysis result shows that the very dominant variable which influences the pornography media explanation effect is from friends influency with the P score = 0,0000 and OR score = 13, 719. The other factor which is related to the research is from the sex factor whose Pv score 0.043 (<0,05) and OR score = 3,71, the explanation frequency has the Pv score 0.005 (P<0.05) with the OR score = 6,50. The acces to the media sources has the Pv score 0.020 (0,05) with the OR score = 3,513. The knowledge has the Pv score 0.020 (o.05) and the OR score = 0,047. The result of this research is that the very dominant factors come from the friends sides while the related factors are from ages, explanation frequency, distance/access to the mass media and knowledge, and the confounding variable is the media types, religions, ages and teenagers personality traits